Conditional cash transfers and high school attainment: Evidence from a large-scale program in the Dominican Republic - Hernandez, Manuel A.; Pellerano, Jose A.; Sanchez, Gonzalo E. (International Food Policy Research Institute, 2022)
Conditional cash transfer (CCT) programs are widely implemented in developing countries but evidence of their medium- and long-term effects on educational achievements is still relatively scarce. This paper examines the impact of a large-scale CCT program on high school attainment in the Dominican Republic. We implement a quasi-experimental approach combining extensive educational, administrative, and household records from program participants across the country and exploiting variations in the scheme (amount) of school transfers received among program participants. We find that receiving additional transfers specific for high school education is, on average, associated with an 11.7-13.2 percentage points higher probability of completing high school relative to not receiving these transfers. We do not find major differences across urban and rural areas nor between female and male students. The transfers seem to play an important role during the last high school year of targeted students. The estimated impacts point to non-negligible effects on employment, salaries, and delayed parenthood. Several robustness checks support our findings.